Bordering and Ordering the Twenty-first Century : Understanding Borders. - Popescu, Gabriel (Human Geography in the Twenty-First Century: Issues and Applications., 2011)
This timely book introduces readers to the central question of borders in the twenty-first century. After familiarizing readers with border thinking and making from antiquity to the present, Gabriel Popescu turns a critical eye on current border-making concepts, processes, and contexts. Throughout, he offers a balanced understanding of borders, explaining why and how interstate borders have emerged, whose interest they serve, who is involved in border making, and how border-making practices affect societies. Assessing the latest theoretical approaches to border studies, the author deftly incor.